화학사고 초기대응 소방대 보호를 위한 독성농도(T-LOC) 끝점거리 연구 - 윤종찬; Jong Chan Yun; 조철희; Chul Hee Cho; 원정훈; Jeong Hun Won (한국안전학회지, 2023)
The purpose of this study is to propose a quantitative toxicity endpoint distance suitable for the initial response of firefighters by comparing and analyzing the commonly applied toxic level of concern (T-LOC), specifically emergency response planning guidelines (ERPG), acute exposure guideline levels (AEGL), and immediately dangerous to life or health (IDLH). This is to protect the fire brigade, which responds to toxic chemical accidents first during the golden time. Using areal locations of hazardous atmospheres, a damage prediction program, the amount of leakage for both acidic and basic substances, along with the endpoint distance, were analyzed for alternative accident and worst-case accident scenarios. The results showed that the toxicity endpoint distance, serving as a compromise between Level-3 and Level-2 of T-LOC, was longer than ERPG-3 and shorter than ERPG-2 with IDLH, while its values were analyzed in the order of ERPG-2, AEGL-2, IDLH, AEGL-3, and ERPG-3. It is suggested that the application of IDLH in an emergency (red card) and ERPG-2 endpoint distance in a non-emergency (non-red card) can be utilized for the initial response of the fire brigade.